The Relationship Between Anger, Childhood Maltreatment, and Emotion Regulation Difficulties in Intimate Partner and Non-Intimate Partner Violent Offenders. (November 2014) - Gardner, Frank L.; Moore, Zella E.; Dettore, Melissa
Violence is a significant public health problem, which has been linked to the primary emotion of anger. While several theoretical models have attempted to understand the relationship between anger and violence, empirical evidence to support these models and the psychological treatments that follow from them have been lacking. A newer model for understanding the relationship between anger and violence emphasizes the dual diatheses of childhood maltreatment and difficulties in emotion regulation as central to understanding the anger−violence relationship. Investigating the relationship between childhood maltreatment and anger experience and expression among 88 violent offenders referred for intimate partner or non-intimate partner violent offenses, results herein confirm that substantial childhood maltreatment is found among violent offenders, with differing patterns of abuse noted across groups. Furthermore, mediational analyses indicate that difficulties in emotion regulation mediate the relationship between childhood maltreatment and various aspects of anger experience and expression among both types of offenders.